Dinamis-Rasionalis dalam Pemikiran Thaha Husain pada Problematika Peradaban Islam dan Barat - Wasid, Wasid (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2013)
The inter-civilization dialogue is necessary: unavoidable. There is no civilization can improve its self without an interaction with other civilization. This phenomenon brings Thaha Husain to review how the civilization of Egypt could be “out of date” compared with the Western civilization. He assumes that it was because of traditional thinking of Muslims. In his opinion, Muslims believe that Islamic tradition is the perfect one: no need to learn from other tradition. Husain talks that to realize this decline is better than to feel perfect (apology). According to Husain, Muslims should learn from history, learn from Western civilization—which is more advanced. In this context, academic fairness is very important for Muslim intellectual to create an academic tradition. Husain supposes that imitating the tradition of the West doesn’t mean imitating its religion. Humanity is the key. From Thaha Husain’s thinking, there are two lessons that can be contemplated. First, life in the tradition is a necessity as life in modern culture. Therefore, there is no tradition which does not accept change and debate in line with the dynamics of humanity. Second, rational approach, scientific and historical criticism is of capital importance to catch up with Western civilization